Introduction to information flow management (IFC) - Umurzakov O. Sh.; Karshiev Z. A. (International Journal on Human-Computing Studies, 2021)
Data flow management is very important today. The article discusses security and integrity in data flow management, tags, explicit and implicit flows, and the level of granularity.